Prednisone treatment in infertile patients with oligozoospermia and accessory gland inflammatory alterations. (26th January 2017) - Milardi, D.; Luca, G.; Grande, G.; Ghezzi, M.; Caretta, N.; Brusco, G.; De Filpo, G.; Marana, R.; Pontecorvi, A.; Calafiore, R.; Foresta, C.; Garolla, A.
Summary: The association between inflammation of the male reproductive system and oligozoospermia has been frequently reported in the clinical work‐up of male infertility. To improve sperm parameters in infertile patients with genital inflammation, many phytochemical and nutraceutical drugs are currently being used. However, their use is still empirical and no conclusive data have been provided about their efficacy. The treatment with steroid anti‐inflammatory drugs might be useful in reducing inflammation and improving sperm parameters, thus increasing the fertility outcome. The aim of this study was to evaluate if glucocorticoid treatment improves seminal parameters in infertile oligozoospermic patients presenting signs of accessory gland inflammation at genital ultrasound. A total of 90 infertile patients were enrolled in the study. They presented normal testicular volume, normal FSH plasma levels, the presence of various degrees of oligozoospermia, associated with scrotal and trans‐rectal ultrasound signs indicative of accessory gland inflammation, but negative microbiological analysis on semen and/or prostatic secretions. Patients were randomly allocated into three groups of treatment, receiving, respectively, 5, 12.5, and 25 mg daily oral Prednisone for one month. Seminal parameters were evaluated at admission and after treatment. In patients undergoing Prednisone treatment at a daily dose of 5 mg we observed a significant increase in total sperm count. At a daily dose of 12.5 mg, Prednisone treatment improved sperm concentration, total sperm count, and the percentage of sperm motility. Twenty‐five mg of Prednisone led to significant improvement in all the sperm parameters, except for semen volume. These results clearly demonstrate that Prednisone treatment can significantly improve sperm parameters in a selected population of oligozoospermic patients. These findings suggest that Prednisone treatment should be considered in idiopathic oligozoospermic patients with supposed normal spermatogenesis and accessory gland inflammatory alterations, in order to improve sperm parameters and fertility outcome.